Short-term effects of ambient particulate matter on blood pressure among children and adolescents:A cross-sectional study in a city of Yangtze River delta, China. (December 2019) - Yang, Hai-bing; Teng, Chen-gang; Hu, Jia; Zhu, Xiao-yan; Wang, Ying; Wu, Jing-zhi; Xiao, Qi; Yang, Wei; Shen, Hui; Liu, Fang
Abstract: Several studies have demonstrated associations between short-term exposure to particulate matter (PM) and blood pressure (BP) among various adults groups, but evidence in children and adolescents is still rare. In 2016, a cross-sectional survey was conducted among 194 104 participants aged 6–17 years in Suzhou, China. Daily concentrations of particulate matters with an aerodynamic diameter of ≤10 μg/m 3 (PM10 ) and aerodynamic diameter ≤2.5 μg/m 3 (PM2.5 ) on 0–6 days preceding BP examination were collected from nearby air monitoring stations. Using generalized linear mixed-effects models, short-term effects of PM on personal BP were estimated. A 10 μg/m 3 increment in the 0–6 day mean of PM2.5 was significantly associated with elevation of 0.20 mmHg [95% confidence interval (95% CI) 0.16–0.23] in systolic BP (SBP), 0.49 mmHg (95% CI 0.45–0.53) in diastolic BP (DBP), respectively. Similarly, 0.14 mmHg (95% CI 0.12–0.16) higher SBP and 0.32 mmHg (95% CI 0.30–0.34) higher DBP were found for each 10 μg/m 3 increase in 0–6 day mean of PM10 . More apparent associations were observed in females than in males. Odds ratio (95%CI) of for PM2.5 exposure at 0–6 d mean was 1.06 (1.03–1.08) in females, while it was 1.01 (0.99–1.03) in males. Participants with young ages, underweight and obesity were also associated with increased susceptibility to PM-induced BP effects. Short-term exposure in PM was significantly associated with elevated BP in children, indicating a need to control PM levels and protect children from PM exposure in China. Highlights: Exposure to elevated PM2.5 and PM10 were associated with increased blood pressure in children and adolescents. Female and young children were more susceptible to PM-induced blood pressure changes. It highlighted the importance of keeping healthy weight against PM exposure. No significantly different relationships between PM2.5 exposure and PM10 with blood pressure changes were observed.